Analisis Beberapa Faktor Yang Mempengaruhi Kinerja Karyawan Badan Penanaman Modal Dan Perizinan Terpadu (Bpmpt ) Kota Surakarta - Friska, Eka Devi; , Drs. Kusdiyanto, S.E., M.Si (2016)
he purpose of this research is to find out some factors affecting BPMPT Surakarta City employee performance, including work discipline, work environment, and work pleasure. The type of this research is a survey research, with quantitative approach. Testing method applied in this research are research instrument tests including validity and reliability test, classic assumption tests that is normality test, hypothesis tests including multiple linear regression test, t test, F test, and coefficient of determination test or R2. The data used in this research is primary data, which is obtained by dsitributing questionnaires to respondents (BPMPT Surakarta City employee). We took 39 employees for samples in this research. Based on the research result, work discipline variable is the dominant variable affecting employee performance. Furthermore, the research shows that there is simutaneous effect between work discipline, work environment, work pleasure and employee performance. Coefficient of determination number or R2 obtained is 58,2%. The variation of change on employee performance were caused by the change of work discipline, work environment, and work pleasure variable. While the 41,8% were caused by another factor which were not analyzed in this research.